Gender Trends in Southeast Asia : Women Now, Women in the Future - Devasahayam, Theresa W. (Book collections on Project MUSE., 2009)
As a region, Southeast Asia has undergone enormous economic and social changes in the last few decades. Women as a collective have seen their lives transformed as a result of rapid development and economic growth. In exploring the progress made by Southeast Asian men and women, this book seeks to answer the following questions: (a) In what areas have women been able to achieve parity with men? (b) In what areas do women encounter specific disadvantages based on their gender as compared with m ...